Why primary prevention is important, and how to promote resilience: CADCA. Issue 6 (7th February 2020) - Knopf, Alison
Abstract : Last week's annual leadership meeting of Community Anti‐Drug Coalitions of America (CADCA) focused, as it always does, on primary prevention. This is defined as preventing the use of drugs (including alcohol), mainly in youth. There were more than 3, 200 attendees, 500 of whom were middle and high schoolers drawn from the coalitions funded by the Drug‐Free Communities (DFC) program, with CADCA member organizations benefiting from training in how to use this funding.